(untitled) (Revista Educação, Artes e Inclusão, 2023)
This study analyzed the role that the school has in constituting the identity of people with disabilities, pointing out its possibilities and limits. To accomplish these purposes, the study addresses the concept of disability produced from the 19th century onwards, from the discussions of authors such as Foucault, Vigotski, Skliar and others, who understand disability as a social construction, defined from the established relationships in the sociocultural context. In addition to the theoretical study, a field research was also carried out, through a narrative interview with to women with disabilities, one graduated in Psychology, and the other in Psychology. The results showed that the school has an important role in the constitution of the identity of people with disabilities, as this one of the most significant social groups that the subjects integrate throughout their lives. It can either contribute to the constitution of an autonomous and confident subject, who realizes its power, as it can constitute insecure people who perceive themselves as deformed/ wrong. In this matter, school can either welcome people in their subjectivity, or exclude them from their formative processes.